2009
DOI: 10.1007/s10661-009-0875-z
|View full text |Cite
|
Sign up to set email alerts
|

The chemical oceanographic consequences of environmental restoration projects in the Golden Horn estuary (Marmara Sea, Turkey)

Abstract: The input of industrial and domestic waste to the horizontal circulation in the Golden Horn Estuary of Marmara Sea has resulted in one of the most polluted estuaries in the past. Consequently, the dissolved oxygen concentrations in both the surface and bottom waters decreased toward to the estuary head during 1998-2005. In contrast, the total suspended solids content of the surface water decreased toward to the estuary mouth. However, construction of the operational collector system surrounding the estuary dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In this study, the highest value of total suspended solid (24.6 mg/L) was determined in bottom water at the Sünnet Bridge, in winter season. Similarly, Balkis et al (2010) reported the highest total suspended solids in the bottom water at Sünnet Bridge station. The high level of total suspended solids indicated that the intense organic, terrestrial and human-induced burdens (micropollutants; hormones) originating from streams and precipitation accumulates in the inner region of the Golden Horn.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In this study, the highest value of total suspended solid (24.6 mg/L) was determined in bottom water at the Sünnet Bridge, in winter season. Similarly, Balkis et al (2010) reported the highest total suspended solids in the bottom water at Sünnet Bridge station. The high level of total suspended solids indicated that the intense organic, terrestrial and human-induced burdens (micropollutants; hormones) originating from streams and precipitation accumulates in the inner region of the Golden Horn.…”
Section: Discussionmentioning
confidence: 83%
“…4 and 5). Balkis et al (2010) reported that the total suspended solids values are higher especially in the inner part of the Golden Horn (ES-SB). Streams, precipitation and terrestrial inputs through the biological activities are responsible for controlling the distribution in the inner regions.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this study can provide considerable knowledge about the sedimentary responses for the restoration of an estuary where multiple human alterations already occurred. Although numerous studies have been conducted for the restoration of altered estuaries, many of them were focused on the improvement of fisheries (Bergstrom et al, 2004;Blomberg et al, 2018) and water quality problems (Smit et al, 1997;Balkis et al, 2010). On the other hand, studies on sedimentary changes for the restoration of an estuary were rare (George et al, 2012) because sedimentary and morphological responses take a relatively long period of time compared to chemical and biological responses.…”
Section: Implications For Future Estuary Managementmentioning
confidence: 99%